Oral narratives as sources for a historical understanding of the lived experience - Robério Americo do Carmo Souza (Revista Maracanan, 2017)
The present paper takes as object of investigation what we call oral narrative having as objective to reflect on how oral narrative can be constructed as a source for a historical understanding of the experiences lived by the narrator in his past frim the way he updates them at the moment of enunciation. Na effort was made to analyze the ways of construction of a narrative identity used by whom tells us their Stories and how this making-oneself produces meaning for the lived experiences in a markedly symbolic plot full of feelings and desires for oneself and for the other the to whom one’s life is narrated.